Optical imaging probes for biomolecules: an introductory perspective. (1st July 2015) - Thomas, Jim A.
Abstract : An overview of optical biomolecular imaging is provided. Abstract : An overview of optical biomolecular imaging is provided. Following a brief history of the development of probes and technologies in this area, general approaches which use biomolecular imaging in current commercial systems are discussed. A brief summary of research challenges in this area – in terms of both the chemistry and technique development – is introduced. Finally, areas rich for possible future development are suggested.